Combining Porcine Xenograft Intra-Corneal Ring Segments and CXL: a Novel Technique - Kanellopoulos AJ (Dove Medical Press, 2019)
Anastasios John Kanellopoulos,1,2 Filippos Vingopoulos1 1Department of Ophthalmology, LaserVision Clinical & Research Eye Institute, Athens, Greece; 2Department of Ophthalmology, New York University Medical School, New York, NY, USACorrespondence: Anastasios John KanellopoulosLaserVision Clinical & Research Eye Institute, Tsocha str. 15 - 17, Athens 115 21, GreeceTel + 30 210 7472777Email ajkmd@mac.comPurpose: The ex-vivo feasibility of creating corneal ring segments (ICRS) from biological tissue (xenograft porcine cornea) and combining intra-corneal implantation with Corneal CrossLinking (CXL).Methods: The ring segments from gamma-irradiated porcine donor cornea were shaped and implanted in human cadaver host cornea using a femtosecond laser for their dissection and host cornea channel preparation. Intra-channel 0.25% riboflavin solution combined with higher fluence CXL of 15 joules total energy followed their implantation. Anterior segment Optical Coherence Tomography (OCT), Scheimpflug tomography and Placido-disc topography were used to monitor the positioning and refractive effect.Results: The novel xenograft ring segments were positioned as planned at 85% corneal depth and mid-peripheral, with documented, up to 7 diopters central cornea flattening.Conclusion: Xenograft intracorneal ring segments combined with CXL may offer an alternative to the synthetic materials used clinically so far, aiming in reducing complications of intracorneal opaque deposit accumulation, segment migration, corneal erosion and potential extrusion. Combining CXL may enhance their refractive effect and stabilize potential or documented host ectasia.Keywords: intrastromal corneal ring segments, gamma-radiated porcine cornea, biological tissue, xenograft corneal surgery, myopia correction, cornea transplantation